Comorbid Diabetes Mellitus in Patients with Coronavirus Disease 2019: A Literature Review - Suyatno Hadi Saputro; Ratna Agustin; Sri Wahyuni; Nur Mukarromah (Indonesian Academia Health Sciences Journal, 2025)
Diabetes Mellitus (DM) is one of the risk factors faced by COVID-19 patients. diabetics aged >60 years, uncontrolled blood sugar levels, and the presence of complications from diabetes with a poor COVID-19 prognosis. In China, the death percentage of diabetics who contracted COVID-19 was 7.3%. In Italy, 36% of deaths in COVID-19 patients are related to diabetes. This study aims to analyze a comprehensive summary of the article Comorbid Diabetes Mellitus in Coronavirus Disease (COVID-19) Patients. Using the literature review method. PubMed, Science Direct and Medica Hospitalia databases. Inclusion criteria: articles on comorbid diabetes mellitus in COVID-19 patients, causes and effects on comorbid diabetes in COVID-19 patients, years from the end of 2019 to 2021, using English and Indonesian, Journal Article and Research article types, availability abstract and full text, Medline journal category. keyword Diabetes Mellitus, COVID-19 obtained 10 articles. COVID-19 patients with diabetes mellitus exhibit a wide range of severity, many of which weigh. Factors whose severity is characterized by age ranging from 50 to 70 years, a history of hypertension, signs and symptoms that are often experienced by COVID-19 patients with diabetes are dyspnea and weakness, laboratory findings show an increase in neutrophils, C-protein reactive, erythrocyte sedimentation rate, procalcitonin, D-dimer, and decreased lymphocytes and albumin. The radiological findings showed a picture of bilateral pneumonia on CT-scan results. The severity and mortality rates vary widely, the severity ranges from 11.1% to 42.4%, and the mortality rate ranges from 15.4% to 42.9%. Comorbidities of diabetes mellitus can increase the severity of COVID-19 patients, there are factors that are related to age, hypertension, symptoms of dyspnea and weakness, inflammation, increased coagulation activity, bilateral pneumonia, high severity and mortality.